The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.2307/583754
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Coping Strategies of Caregivers to Alzheimer's Patients

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. National Council on Family Relations is collaborating with JSTOR to digitize, preserve and extend access to Family Relations.The investigators of this project examined several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
100
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(114 citation statements)
references
References 17 publications
11
100
0
2
Order By: Relevance
“…Demented persons are usually supported by an informal network consisting of among others family and friends. In existing research, actual support from the informal social network has Competence in caregivers 43 been found to diminish caregiver burden [1,20], or to have no effect on the outcomes for caregivers [5,18,21]. Perceived support, as experienced by the caregiver, was found to have a positive effect on the caregiver in two studies where no effects of potential or actual support were found [5,13].…”
Section: Characteristics O F the Demented Person's Social Networkmentioning
confidence: 97%
See 2 more Smart Citations
“…Demented persons are usually supported by an informal network consisting of among others family and friends. In existing research, actual support from the informal social network has Competence in caregivers 43 been found to diminish caregiver burden [1,20], or to have no effect on the outcomes for caregivers [5,18,21]. Perceived support, as experienced by the caregiver, was found to have a positive effect on the caregiver in two studies where no effects of potential or actual support were found [5,13].…”
Section: Characteristics O F the Demented Person's Social Networkmentioning
confidence: 97%
“…The caregiver outcomes have been found to be unrelated to the caregiver's religion [16], socioeconomic status [20,32], or age [20].…”
Section: Characteristics O F the Caregivermentioning
confidence: 99%
See 1 more Smart Citation
“…A logical correlation would suggest that the more difficult caregiving becomes, the more the sense of burden and stress increases. However, specialists have discovered that while the severity of AD is a significant factor, it alone does not correlate with the degree of burden experienced by caregivers (Ory et al, 1984;Pratt et al , 1985;Zarit et al , 1980;Zarit et al , 1985) . Pratt et al (1985) note that stress is reduced if caregivers are confident about their problem-solving and caregiving skills, and are able to reframe or change the meaning of otherwise stressful circumstances .…”
Section: Burdens Of Primary Caregiversmentioning
confidence: 99%
“…However, specialists have discovered that while the severity of AD is a significant factor, it alone does not correlate with the degree of burden experienced by caregivers (Ory et al, 1984;Pratt et al , 1985;Zarit et al , 1980;Zarit et al , 1985) . Pratt et al (1985) note that stress is reduced if caregivers are confident about their problem-solving and caregiving skills, and are able to reframe or change the meaning of otherwise stressful circumstances . Zarit et al (1985) suggest that '\men the caregiver is flexible and tries out new approaches [for managing problems], the burden tends to be experienced as less stressful" (p. 72).…”
Section: Burdens Of Primary Caregiversmentioning
confidence: 99%